Prototype development of VOIP steganography - Al-Othmani, Abdulaleem Zaid Mohammed (2009)
Information Security has evolved significantly over the last decade and even more quickly over the last few years. Most organizations recognize that one of their most important assets is their data. Steganography is an effective means of hiding secret data, thereby protecting the data from unauthorized or unwanted viewing. Indeed, along with encryption, steganography is one of the fundamental ways by which data can be kept confidential. Hiding the desired secret information in seemingly innocent multimedia files or medium will avoid the need to secure communication channel when sending secret messages. The biggest challenge to steganography is how to increase the amount of information to be embedded in the host channel without affecting the properties of that channel while keeping this secret transmission invisible to unauthorized parties. To face this challenge, many methods, media, techniques and algorithms are being introduced. One of the new and promising communication medium that can be used as a host for steganography is Voice over Internet Protocol. VoIP is a form of communication that allows people to make phone calls over an internet connection instead of typical analogue telephone lines. VoIP characteristics, such as, real-time transmission, bi-directional nature and vast amount of data make it very appropriate medium to hide secret data. Few recent researches were conducted to elucidate the steganography techniques and theories that can be applied on VoIP. This project concerns available steganographic techniques that can be used for creating covert channels for VoIP streams. Based on that, the proposed prototype is configured to apply some of these techniques in lab environment. Consequently, some suggested improvements and techniques are introduced in this project report to enhance VoIP steganography.